Building Reflective Practice: Establishing a Sustainable Balint Group Model for Child and Adolescent Psychiatrists in Wales - Megan Davies-Kabir; Andrew Todd (BJPsych Open)
Aims: The project aimed to establish a regular Balint group for Child and Adolescent Psychiatry (CAP) Specialist Resident (SpR) doctors in Wales, support the development of future Balint leaders through training, and enhance the sustainability of these groups. By increasing the number of accredited leaders across Wales, the project sought to expand opportunities for clinicians at various levels to engage in reflective practice, have a safe space to consider their relationship with patients, and ultimately increase levels of emotional capacity and wellbeing.